Persepsi Masyarakat Terhadap Akhlak Remaja Dalam Berinteraksi Sosial Di Desa Purbasari Kec. Tapian Dolok Kab. Simalungun - Nurhalija, Maisya; Putra, Ilham Mirzaya (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research provides a fairly comprehensive picture of the importance of understanding adolescent morals in the social context of society, especially in Purbasari Village. Among the emphases discussed are the role of adolescent morals in social interaction, the urgency of fostering adolescent morals, and the impact of community perceptions on adolescent morals. Descriptions of the definition of adolescence, social change, and the pressures faced by adolescents provide a strong foundation for the reader's understanding of the relevance of this research. This study aims to determine the community's perception of adolescent morals and to determine the morals of adolescents in Purbasari Village, Tapian Dolok Subdistrict, Simalungun Regency. The method used in this research is a descriptive quantitative method that provides a good structure in describing the results of the research. The data collection technique in this research is in the form of observation and distributing questionnaires using a Likert scale. Data validity in this study uses validity and reliability data analysis. The results showed that the community's perception of adolescent morals from the religious, social, and ethical aspects provided deep insight into how the community in Purbasari Village assessed adolescent morals in social interaction. Furthermore, the discussion of community perceptions of adolescent morals provides good insight into the social dynamics in society, the factors that influence community perceptions, and the factors that influence community perceptions.